Acceptability of a Gonococcal Vaccine Among Sexually Active Men Who Have Sex With Men. Issue 1 (January 2022) - Abara, Winston E.; Kirkcaldy, Robert D.; Bernstein, Kyle T.; Zlotorzynska, Maria; Sanchez, Travis
Abstract : Background: Prospects for a gonococcal vaccine have advanced. Vaccine acceptability is crucial to maximizing population-level protection among key groups, such as men who have sex with men (MSM). We assessed the prevalence of gonococcal vaccine acceptability among sexually active MSM in the United States. Methods: We used data from the American Men's Internet Study conducted from August 2019 to December 2019. We calculated frequencies of sociodemographic characteristics, vaccine acceptability, and preferred location for vaccine receipt. Using log-binomial regression analyses, we calculated unadjusted prevalence rates (PRs) and 95% confidence intervals (CIs) to evaluate factors associated with vaccine acceptability. Results: Of 4951 MSM, 83.5% were willing to accept a vaccine and 16.5% were unwilling. Preferred vaccination locations were primary care provider's clinics (83.5%) and sexually transmitted disease (STD) clinics (64.6%). Vaccine acceptability was greater among young MSM (15–24 years [PR, 1.09; 95% CI, 1.05–1.12], 25–29 years [PR, 1.13; 95% CI, 1.09–1.17], and 30–39 years [PR, 1.10; 95% CI, 1.05–1.14] compared with MSM ≥40 years), MSM living with HIV (PR, 1.05; 95% CI, 1.02–1.09), and MSM who reported (in the past 12 months) condomless anal sex (PR, 1.09; 95% CI, 1.06–1.12), a bacterial STD test (PR, 1.18; 95% CI, 1.15–1.21), HIV preexposure prophylaxis use (PR, 1.17; 95% CI, 1.14–1.19), a bacterial STD diagnosis (PR, 1.04; 95% CI, 1.02–1.07), or a health care provider visit (PR, 1.11; 95% CI, 1.06–1.16). Men who have sex with men who reported ⩽high school education (PR, 0.93; 95% CI, 0.91–0.97) were less willing to accept a vaccine compared with those with >high school education. Conclusions: Most respondents were willing to accept a gonococcal vaccine. These findings can inform the planning and implementation of a future gonococcal vaccination program that focuses on MSM. Abstract : A majority of sexually active men who have sex with men in this sample were willing to accept a vaccine, although acceptability varied by certain characteristics. Preferred locations for vaccine receipt were primary care provider's clinics and sexually transmitted disease clinics.Supplemental digital content is available in the text.